SWR1-Independent Association of H2A.Z to the LINC Complex Promotes Meiotic Chromosome Motion - González-Arranz, Sara; Gardner, Jennifer M.; Yu, Zulin; Patel, Neem J.; Heldrich, Jonna; Santos, Beatriz; Carballo, Jesús A.; Jaspersen, Sue L.; Hochwagen, Andreas; San-Segundo, Pedro A. (Frontiers in Cell and Developmental Biology, 2020)
The H2A.Z histone variant is deposited into the chromatin by the SWR1 complex, affecting multiple aspects of meiosis. We describe here a SWR1-independent localization of H2A.Z at meiotic telomeres and the centrosome. We demonstrate that H2A.Z colocalizes and interacts with Mps3, the SUN component of the linker of nucleoskeleton, and cytoskeleton (LINC) complex that spans the nuclear envelope and links meiotic telomeres to the cytoskeleton, promoting meiotic chromosome movement. H2A.Z also interacts with the meiosis-specific Ndj1 protein that anchors telomeres to the nuclear periphery via Mps3. Telomeric localization of H2A.Z depends on Ndj1 and the N-terminal domain of Mps3. Although telomeric attachment to the nuclear envelope is maintained in the absence of H2A.Z, the distribution of Mps3 is altered. The velocity of chromosome movement during the meiotic prophase is reduced in the htz1Δ mutant lacking H2A.Z, but it is unaffected in swr1Δ cells. We reveal that H2A.Z is an additional LINC-associated factor that contributes to promote telomere-driven chromosome motion critical for error-free gametogenesis.